Electrical dry needling as an adjunct to exercise, manual therapy and ultrasound for plantar fasciitis: A multi-center randomized clinical trial. - James Dunning; Raymond Butts; Nathan Henry; Firas Mourad; Amy Brannon; Hector Rodriguez; Ian Young; Jose L Arias-Buría; César Fernández-de-Las-Peñas (PLoS ONE, 2018)
STUDY DESIGN:Randomized, single-blinded, multi-center, parallel-group trial. OBJECTIVES:To compare the effects of adding electrical dry needling into a program of manual therapy, exercise and ultrasound on pain, function and related-disability in individuals with plantar fasciitis (PF). BACKGROUND:The isolated application of electrical dry needling, manual therapy, exercise, and ultrasound has been found to be effective for PF. However, no previous study has investigated the combined effect of these interventions in this population. METHODS:One hundred and eleven participants (n = 111) with plantar fasciitis were randomized to receive electrical dry needling, manual therapy, exercise and ultrasound (n = 58) or manual therapy, exercise and ultrasound (n = 53). The primary outcome was first-step pain in the morning as measured by the Numeric Pain Rating Scale (NPRS). Secondary outcomes included resting foot pain (NPRS), pain during activity (NPRS), the Lower Extremity Functional Scale (LEFS), the Foot Functional Index (FFI), medication intake, and the Global Rating of Change (GROC). The treatment period was 4 weeks with follow-up assessments at 1 week, 4 weeks, and 3 months after the first treatment session. Both groups received 6 sessions of impairment-based manual therapy directed to the lower limb, self-stretching of the plantar fascia and the Achilles tendon, strengthening exercises for the intrinsic muscles of the foot, and therapeutic ultrasound. In addition, the dry needling group also received 6 sessions of electrical dry needling using a standardized 8-point protocol for 20 minutes. The primary aim was examined with a 2-way mixed-model analysis of covariance (ANCOVA) with treatment group as the between-subjects variable and time as the within-subjects variable after adjusting for baseline outcomes. RESULTS:The 2X4 ANCOVA revealed that individuals with PF who received electrical dry needling, manual therapy, exercise and ultrasound experienced significantly greater improvements in first-step morning pain (F = 22.021; P<0.001), resting foot pain (F = 23.931; P<0.001), pain during activity (F = 7.629; P = 0.007), LEFS (F = 13.081; P<0.001), FFI Pain Subscale (F = 13.547; P<0.001), FFI Disability Subscale (F = 8.746; P = 0.004), and FFI Total Score (F = 10.65; P<0.001) than those who received manual therapy, exercise and ultrasound at 3 months. No differences in FFI Activity Limitation Subscale (F = 2.687; P = 0.104) were observed. Significantly (X2 = 9.512; P = 0.023) more patients in the electrical dry needling group completely stopped taking medication for their pain compared to the manual therapy, exercise and ultrasound group at 3 months. Based on the cutoff score of ≥+5 on the GROC, significantly (X2 = 45.582; P<0.001) more patients within the electrical dry needling group (n = 45, 78%) achieved a successful outcome compared to the manual therapy, exercise and ultrasound group (n = 11, 21%). Effect sizes ranged from medium to large (0.53<SMD<0.85) at 3 months in favor of the electrical dry needling group. CONCLUSION:The inclusion of electrical dry needling into a program of manual therapy, exercise and ultrasound was more effective for improving pain, function and related-disability than the application of manual therapy, exercise and ultrasound alone in individuals with PF at mid-term (3 months). LEVEL OF EVIDENCE:Therapy, Level 1b.